HESITAÇÃO VACINAL EM RESIDENTES DE CAMPO GRANDE, MATO GROSSO DO SUL, BRASIL - ANA ISABEL DO NASCIMENTO (2024)
A vacination is the most cost effective measure for controlling preventable diseases. However, declining vaccination coverage percentages have favored the re emergence of some controlled diseases in Brazil and worldwide. Vaccine hesitancy, occurring between complete acceptance and total refusal of vaccines, contributes to the decline in vaccination coverage. Understanding the reasons for hesitancy and identi fying those amenable to intervention is essential for planning actions to increase vaccination coverage. This study aims to assess vaccine hesitancy among residents of Campo Grande, Mato Grosso do Sul, Brazil. It is a descriptive cross sectional study conducted concurrently with a population based household survey estimating vaccination coverage in the city's urban area from November 2022 to October 2023. Cluster sampling in two stages was used to select data collection sites following the World Health Orga nization (WHO) method, utilizing the 2021 census tract grid from the Brazilian Institute of Geography and Statistics (IBGE). The first sampling stage resulted in 30 clusters. After defining clusters, households to be visited and included in the study were randomly selected (second stage). All residents aged 12 and older who agreed to participate were included. Data were collected using the vaccine hesitancy questionnaire developed by the WHO's Strategic Advisory Group of Experts on Immunization (SAGE). Uni and multivariate analyses were used to assess the association between vaccine hesitancy and other study variables. At the study's conclusion, 518 residents of the general population were interviewed. Among them, 158 were parents of children under 12 and an swered questions about vaccine hesitancy related to childhood vaccination. Vaccine hesitancy was 50.19% in the general population and 39.24% among parents. Hesitant participants in the general population were younger, had less belief in vaccination efficac y, and predominantly sought vaccine information through television and social media. Lack of confidence in vaccination safety was the most frequent cause of hesitancy. The most cited complacency reason was the perception that the vaccine was unnecessary, and the main convenience reason was not knowing where to obtain reliable vaccine information. These reasons were mainly mentioned after the start of the COVID 19 pandemic. The study results highlight the need to identify population uncertainties and fears r egarding vaccines with empathy and collaboration between healthcare professionals and the population to reduce the impact of vaccine misinformation. This approach aims to promote collective and individual awareness of the importance of immunization among r esidents to foster lasting vaccine acceptance.